PENGEMBANGAN MEDIA PEMBELAJARAN MINIATUR PATAYA (PETA BUDAYA) PADA PEMBELAJARAN IPS KELAS IV SD NEGERI 96 PALEMBANG - Yulia Permata Sari; M. Juliansyah Putra; Sunedi (STKIP Subang, 2023)
Based on the problems at SD Negeri 96 Palembang, the lack of use of social studies learning media makes it difficult for students to understand the material of theme 7 subtheme 2 Indanhya ethnic and religious diversity in my country. This study aims to produce learning media miniature pataya (cultural map) that is valid, practical and potential effects. The type of research method used is Research and Development (R&D) with the ADDIE model. Based on the analysis of the needs of student learning outcomes, it is known that out of 26 students only 3 students have not reached the KKM score while the other 3 students are still below the kkm so that there are students who still do not understand the Beautiful Material of ethnic and religious diversity in my country. Development of Learning Media Miniature Pataya (Cultural Map) in Social Studies class IV SD Negeri 96 Palembang has produced learning media products that have been declared valid by media, material and language experts. The results of the Miniature Pataya media research were declared valid with an average result of 86.45% with the category